2022
DOI: 10.1098/rspb.2022.1223
|View full text |Cite
|
Sign up to set email alerts
|

Niche construction through a Goldilocks principle maximizes fitness for a nest-sharing brood parasite

Abstract: Generalist brood parasites that share nests with host nestlings can optimize resource acquisition from host parents by balancing the benefits that host nest-mates provide, including attracting increased provisions to the nest, against the costs of competing with the same host young over foster parental resources. However, it is unclear how parasitic chicks cope when faced with more nest-mates than are optimal for their survival upon hatching. We suggest that, in the obligate brood parasitic brown-headed cowbir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 35 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…The subject of brood parasitism has become the focus of widespread attention for the numerous finely tuned adaptations that have been discovered in coevolving specialist brood parasite–host systems (Davies, 2000; Krüger, 2007; Soler, 2017a). A recent study by Antonson et al (2022) claims to have found one of these fascinating adaptations, posing the exciting conclusion that brown‐headed cowbird ( Molothrus ater ) chicks use a niche construction strategy (alteration of its own environment for its own fitness benefit) in prothonotary warbler ( Protonotaria citrea ) host nests. In this experimental study, the authors have found that the selective brood reduction strategy driven by cowbird nestlings is reducing, but not eliminating host broods.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The subject of brood parasitism has become the focus of widespread attention for the numerous finely tuned adaptations that have been discovered in coevolving specialist brood parasite–host systems (Davies, 2000; Krüger, 2007; Soler, 2017a). A recent study by Antonson et al (2022) claims to have found one of these fascinating adaptations, posing the exciting conclusion that brown‐headed cowbird ( Molothrus ater ) chicks use a niche construction strategy (alteration of its own environment for its own fitness benefit) in prothonotary warbler ( Protonotaria citrea ) host nests. In this experimental study, the authors have found that the selective brood reduction strategy driven by cowbird nestlings is reducing, but not eliminating host broods.…”
mentioning
confidence: 99%
“…This also implies an active manipulation of their environment (the nest), and therefore, this strategy could also be considered niche construction. However, Antonson et al (2022) suggest that in the brown‐headed cowbird—protonotary warbler system, the brood parasite selectively manipulates brood reduction favouring the presence of two warbler nestlings in the nest. This suggestion is based on comparisons of data on nestling warbler mortality in four experimental groups, with two parasitized and two unparasitized treatments.…”
mentioning
confidence: 99%
See 3 more Smart Citations